2020
DOI: 10.1103/physrevd.102.045018
|View full text |Cite
|
Sign up to set email alerts
|

Vortices in Maxwell-Chern-Simons-Higgs models with nonminimal coupling

Abstract: We investigate the presence of vortex configurations in generalized Maxwell-Chern-Simons models with nonminimal coupling, in which we introduce a function that modifies the dynamical term of the scalar field in the Lagrangian. We first follow a route already considered in previous works to develop the Bogomol'nyi procedure, and, in this context, we use the first-order equations to obtain a vortex with a novel behavior at its core. We then go further and introduce a novel procedure to develop the Bogomol'nyi me… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 56 publications
(173 reference statements)
0
13
0
Order By: Relevance
“…This function W is inspired in the work [34] and it has been used before in several distinct situations as, for instance, in Refs. [15,17,19]. Notice the presence of the factor 1/r in the last term; it is important since, under integration to get the energy, the line element dx dy = r dr dθ makes dW/dr be a surface term after integration.…”
Section: First Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…This function W is inspired in the work [34] and it has been used before in several distinct situations as, for instance, in Refs. [15,17,19]. Notice the presence of the factor 1/r in the last term; it is important since, under integration to get the energy, the line element dx dy = r dr dθ makes dW/dr be a surface term after integration.…”
Section: First Modelmentioning
confidence: 99%
“…The use of a field-dependent function coupled with the gauge field dynamical term has also been recently considered in [14] in the electric context, that is, in the presence of an electric charge fixed at the origin; there, we showed that the electric field has a behavior that captures the basic feature of asymptotic freedom, an effect that is usually associated to quarks and gluons. It was also considered, for instance, in [15][16][17][18][19] to describe vortex configurations with internal structures in the plane in the magnetic context. Moreover, very recently, in [20] the authors studied the dielectric Skyrme model, that is, the Skyrme model where both the kinetic and Skyrme terms are multiplied by field-dependent functions, leading to new results of current interest.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Looking at (24) and ( 25), we can clearly see that at the limit of λ → 0, the gauge field assumed a constant behavior, i. e., a(r) = a 0 . Meanwhile, we have f (r) ∝ r a 0 , which gives us non-topological field configurations.…”
Section: Description Of the Theorymentioning
confidence: 99%
“…As a motivation for the study of these structures we have some applications such as: in the study of vortices in topological superconductors [3], the study of topological structures in twodimensional quantum gravity [21], topological solutions describing the multivortex dynamics in Abelian theories [22], structures in models with k-defects [23], study of generalized models [24][25][26][27][28][29] and non-generalized ones [30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%